Integration of Safety Concerns and Societal Impact as Learning Outcomes of Mechanical Engineering Courses - Yakub, B; Naik, Santosh Madeva; Unnisa, Azeem (Journal of Engineering Education Transformations, 2019)
For many homework, mini and final projects in all the courses that the author taught since the last more than 5 years, the students were asked as a part of course requirements to include critical real life examples, and a discussion of how poorly designed mechanical components or subsystems can cause safety concerns and affect the society at large in one way or the other. These requirements partially address some of the students' outcomes under General ABET's Criterion 3. Of particular interest are the students' understanding of the professional ethics (outcome 'f'), and understanding the impact of engineering solutions and how they impact the society (outcome 'h'). In order to help in identifying some of the real life engineering components, the author showed online videos and also used "Touch and fell" (T&F) idea in which some of the failed or non-functioning engineering components (shafts, bearings, bolts, etc.) were brought to the class to do first order reverse engineering (reconstruction of failures using mechanics approach). While few junior and senior level textbooks in the Mechanics, Design, Thermal Sciences and Production areas do include few worked examples and exercise problems based on real life industry applications, they do not generally include a discussion based on the final results from ethical or societal impact points of view. Also, most chapter-end exercise problems are usually structured based on directly using concepts and formulas from the chapter and not necessarily require a realization of real life applications of such problems. Usually, this may be beyond the scope of some classes, or, it may be perhaps due to the time constraints faced by instructors, or, due to lack of maturity level of students. Similar is the experience with the openended mini-projects such books may suggest. On another issue, some of the instructors may not have enough industry exposure to think of real life applications of homework problems and project assignments.